Political Alignment, Attitudes Toward Government and Tax Evasion - Julie Berry Cullen; Nicholas Turner; Ebonya Washington (Center for Economic Studies and ifo Institute (CESifo), 2018)
We ask whether attitudes toward government play a causal role in the evasion of U.S. personal income taxes. We first use individual-level survey data to demonstrate a link between sharing the party of the president and trust in the administration generally and opinions on taxation and spending policy, more specifically. Next, we move to the county level, and measure tax behavior as elections, decided by the voting behavior in swing-states, push voters in partisan counties into and out of alignment with the party of the president. Using IRS data, we find that reported taxable income increases as a county moves into alignment, with the increases concentrated in income sources that are easily evaded, due to lack of third-party reporting. Corroborating the view that evasion falls, potentially suspect EITC claims and audit rates also fall. Our results provide real-world evidence that a positive outlook on government lowers tax evasion.
Keywords: D72; H24; H26; H30; 330; tax evasion; tax morale